Antiphospholipid Antibodies Affect Human Endometrial Angiogenesis: Protective Effect of a Synthetic Peptide (TIFI) Mimicking the Phospholipid Binding Site of β2glycoprotein I. (7th May 2013) - Di Simone, Nicoletta; D'Ippolito, Silvia; Marana, Riccardo; Di Nicuolo, Fiorella; Castellani, Roberta; Pierangeli, Silvia S.; Chen, Pojen; Tersigni, Chiara; Scambia, Giovanni; Meroni, Pier Luigi
<x xml:space="preserve">Abstract</x> Problem Aim of our study was to investigate whether TIFI, a syntetic peptide able to compete with anti‐phospholipid antibodies (aPL) in the binding to endothelium, may restore aPL‐inhibited endometrial angiogenesis. Methods The protective role of TIFI was evaluated on: i) aPL–inhibited of human endometrial endothelial cells (HEEC) angiogenesis in vitro; ii) aPL–inhibited vascular endothelial growth factor (VEGF) and metalloproteases (MMPs) expression; iii) aPL‐inhibited Nuclear Factor‐κB (NF‐κB) and Extracellular signal–Regulated Kinase (ERK) activation and (iv) angiogenesis in vivo. Results TIFI restores in a dose‐dependent manner: i) aPL‐mediated inhibition of HEEC angiogenesis in vitro and in vivo (P < 0.05), ii) VEGF (P < 0.001) and MMP–2 (P < 0.05) expression and iii) NF‐κB DNA binding and ERK–1/2 activation (P < 0.05) inhibited by aPL. Conclusion Our results show for the first time the protective effects of TIFI, as represented by its ability to interfere with aPL mediated anti‐angiogenic activity.